Availability and Utilisation of Science Laboratory Facilities on Science Teacher-Trainees’ Pedagogical Content Knowledge in Science - Nelson Mandela Anane; Vincent Anum Ankamah-Lomotey (Phenomenon : Jurnal Pendidikan MIPA, 2023)
This study assessed final-year science teacher-trainee perceptions of the impact of the availability and utilization of laboratory facilities on science students' pedagogical content knowledge (PCK) in science at Accra and Ada Colleges of Education. This research was motivated by an initial study that stated that the majority of junior high school science teachers were unable to teach science effectively so it was easier for students to understand. This research used a quantitative approach with a cross-sectional descriptive survey design involving 62 intern teachers, 15 science tutors, and two school principals. The research instrument (tutor and teacher questionnaire) was declared suitable for use after a slight revision with the Validity and Reliability scores of 0.84 and 0.86. The research revealed that final-year science teacher candidates at the Accra College of Education were of the opinion that the availability and utilization of laboratory facilities had a moderate but neutral impact on PCK in science, in contrast to the results of research by science teachers at Ada College which stated that the availability and use of Laboratory facilities have a high and positive impact on PCK Science. It is recommended that science tutors engage science trainee teachers in efficient hands-on activities, and also focus on on-campus and off-campus practicums to develop the training of PCK science trainee teachers.Keywords: Laboratory Facilities, Science Teacher-Trainees, Pedagogical Content Knowledge (PCK in Science, Impact of Availability and UtilisationStudi ini menilai persepsi guru-peserta pelatihan sains tahun terakhir tentang dampak ketersediaan dan pemanfaatan fasilitas laboratorium terhadap pengetahuan konten pedagogis siswa sains (PCK) dalam sains di Accra dan Ada Colleges of Education. Penelitian ini dilatarbelakangi oleh penelitian awal yang menyatakan bahwa sebagian besar guru IPA SMP belum mampu mengajarkan IPA secara efektif sehingga lebih mudah dipahami oleh siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei deskriptif cross-sectional yang melibatkan 62 orang guru magang, 15 orang tutor IPA, dan dua orang kepala sekolah. Instrumen penelitian (angket tutor dan guru) dinyatakan layak digunakan setelah dilakukan sedikit revisi dengan skor Validitas dan Reliabilitas sebesar 0,84 dan 0,86. Hasil penelitian mengungkapkan bahwa calon guru IPA tingkat akhir di Accra College of Education berpendapat bahwa ketersediaan dan pemanfaatan fasilitas laboratorium berdampak sedang namun netral terhadap PCK bidang IPA, berbeda dengan hasil penelitian guru IPA di Ada College yang menyatakan bahwa ketersediaan dan pemanfaatan fasilitas Laboratorium memberikan dampak yang tinggi dan positif terhadap PCK Sains. Disarankan agar tutor sains melibatkan guru peserta pelatihan sains dalam kegiatan praktik langsung yang efisien, dan juga fokus pada praktik di dalam kampus dan di luar kampus untuk mengembangkan pelatihan guru peserta pelatihan sains PCK.